2016
DOI: 10.4236/ojd.2016.53003
|View full text |Cite
|
Sign up to set email alerts
|

Depression and Hopelessness in Institutionalized Elderly: A Societal Concern

Abstract: Even though occurrence of depression in older adults is considered a major public health problem, very few Indian studies have made an attempt to study the mental health of elderly residing in institutionalized settings such as nursing homes and old age homes. The purpose of this study is to examine the presence and severity of depression and extent of negative attitudes about the future in institutionalized elderly in India. Data were collected by administering the Beck Depression Inventory (BDI) and Beck Hop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 22 publications
1
7
0
1
Order By: Relevance
“…In the network of depressive symptoms in elderly patients, feeling hopeless and the level of energy are the most pivotal nodes. This is consistent with other findings of depressive symptoms in older patients (Hill, Gallagher, Thompson, & Ishida, 1988; Sarin, Punyaapriya, Sethi, & Nagar, 2016; Zengarini et al, 2016). Older patients often lose hope of remission in light of their age.…”
Section: Discussionsupporting
confidence: 93%
“…In the network of depressive symptoms in elderly patients, feeling hopeless and the level of energy are the most pivotal nodes. This is consistent with other findings of depressive symptoms in older patients (Hill, Gallagher, Thompson, & Ishida, 1988; Sarin, Punyaapriya, Sethi, & Nagar, 2016; Zengarini et al, 2016). Older patients often lose hope of remission in light of their age.…”
Section: Discussionsupporting
confidence: 93%
“…8 They used, in a sample of 79 elderly people, a socio-demographic questionnaire and questions about reading behavior and the use of the internet/computer, which is the main approach to be correlated with hopelessness in the elderly. Beck's Hopelessness Scale was used, composed of 20 sentences of true or false that classify the level of hopelessness at the minimum level of hopelessness (0-3), mild level of hopelessness (4)(5)(6)(7)(8), moderate level of hopelessness (9)(10)(11)(12)(13)(14) and serious level (greater than 14). Finally, a question was made on the Reading Attitude Scale, composed of 30 assertions related to reading behavior in which maximum score is 120 points.…”
Section: Resultsmentioning
confidence: 99%
“…The sense of hopelessness reflects a negative view of the future that reinforces depressive thoughts. 14 A study evidenced the significant relationship between anxiety, depression and hopelessness among the 76-elderly surveyed.³ It may be hypothesized that typical aging feelings can arouse hopelessness and lead to depressive and anxious symptoms. The advancing age courses with a progressive loss of physical, mental and social resources, leading to feelings of helplessness, leading to feelings of impotence and fragility.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was found that the hopelessness levels of the older adult population who were not infected during the outbreak period were below the middle level. Sarin et al ( 2016 ) found in their study that the hopelessness level of older adults was moderate, Şahin et al ( 2018 ), Choi et al ( 2016 ) stated that older adults have high levels of hopelessness. The fact that this research was conducted during the COVID-19 outbreak is thought to have an impact on the level of hope.…”
Section: Discussionmentioning
confidence: 97%